Diseminasi Teknologi Mesin Perajang Tembakau dalam Upaya Menerapkan Ekoteknologi di Desa Tumbrasanom Kecamatan Kedungadem Kabupaten Bojonegoro - Mega Novita; Achmad Buchori; Ali Mujahidin (Universitas Islam Nahdlatul Ulama Jepara, 2019)
The villagers of Tumbrasanom have 4 business groups, namely prosperous farmers, totaling 40 people, who do not have automatic tobacco chopper tools. In the manufacture and marketing of tobacco chopper products in the village of Tumbrasanom it is still simple. Then the marketing of its products has not been done online and there is no partner network, therefore it needs to be given a touch of appropriate technology that is environmentally friendly by using automatic tobacco chopper. The activity of disseminating technology products to the public aims to improve the welfare of citizens through increasing tobacco production capacity with automatic tobacco chopper tools using ecotechnology strategies, as well as increasing the value of sales and marketing. Outputs that have been generated from this activity include the development of a number of group members, training in the use and maintenance of automatic tobacco chopping tools, training in the use of automatic tobacco chopper tools, training in tobacco processing and good financial management training and sales and marketing of tobacco products and chopper machines automatic tobacco. The automatic tobacco chopper tool produced is 8 pieces with a capacity of 5 kg/ minute